2011
DOI: 10.1111/j.1435-5957.2010.00343.x
|View full text |Cite
|
Sign up to set email alerts
|

The impact of urban growth on commuting patterns in a restructuring city: Evidence from Beijing

Abstract: Our existing knowledge of the links between urban growth and commuting patterns are dominated by cases from developed countries. This paper examines the impact of urban growth on workers' commutes using the case of Beijing, which is undergoing rapid economic and spatial restructuring. The results of an analysis of household survey data show that clustered and compact urban development in planned sub-centres is likely to reduce suburban workers' need for a long-distance commute to the city centre when the worke… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
46
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 83 publications
(50 citation statements)
references
References 76 publications
4
46
0
Order By: Relevance
“…This 'commuting paradox' was explained by the likelihood that households and firms were rationally relocating to reduce commuting times, and that this spatial adjustment can be more easily made in dispersed metropolitan space with many alternative employment centers and residential location choices (Gordon et al 1991;Levinson and Kumar 1994;Sultana 2000). Dubin (1991), Crane and Chatman (2004), Zhao et al (2011) all found that the decentralization of employment to the suburbs decreased commuting times. On the other hand, Sultana and Chaney (2003) and Weber and Sultana (2007) showed that commuting times are higher in areas with low density.…”
Section: Impacts Of Sprawl On Urban Transportationmentioning
confidence: 99%
“…This 'commuting paradox' was explained by the likelihood that households and firms were rationally relocating to reduce commuting times, and that this spatial adjustment can be more easily made in dispersed metropolitan space with many alternative employment centers and residential location choices (Gordon et al 1991;Levinson and Kumar 1994;Sultana 2000). Dubin (1991), Crane and Chatman (2004), Zhao et al (2011) all found that the decentralization of employment to the suburbs decreased commuting times. On the other hand, Sultana and Chaney (2003) and Weber and Sultana (2007) showed that commuting times are higher in areas with low density.…”
Section: Impacts Of Sprawl On Urban Transportationmentioning
confidence: 99%
“…Recently some studies were done on specific aspects of travel behaviour in individual Chinese cities (e.g. mode choice in Nanjing by Feng et al 2014) and only for Jinan (Jiang et al 2014) and Beijing (Yang 2006;Ma et al 2015;Zhao et al 2010Zhao et al , 2011 empirical studies are done that link travel behaviour to changes in the urban fabric. These studies are all based on case studies for a single city, mostly Beijing, and focus on the importance of neighbourhood characteristics at the individual city level, rather than aggregate city-wide characteristics.…”
Section: Introductionmentioning
confidence: 99%
“…In Beijing, China, employees in the manufacturing sector appear to have shorter commutes and travel within the planned suburban sub-centres. This indicates that the decentralization of employment in the manufacturing sector offers greater opportunities to improve the spatial balances between residential and workplace location choices (Zhao et al, 2011b). Lee et al (2006) indicated that in US metropolitan areas, the average commuting duration did not grow substantially in the 1990s, when these areas observed a significant decentralization of employment.…”
Section: 132mentioning
confidence: 96%
“…A study by Zhao et al (2011b) suggests that the likelihood of commuting to other areas in the suburbs grows when accessibility to transport is high. As indicated by Zhao et al (2011b), the main reason may be that improved public transport can decrease people's travel costs and thus allow them to be more mobile.…”
Section: Massive Public Transport Investmentmentioning
confidence: 97%
See 1 more Smart Citation